2015
DOI: 10.1097/dss.0000000000000162
|View full text |Cite
|
Sign up to set email alerts
|

Prolonging the Duration of Masseter Muscle Reduction by Adjusting the Masticatory Movements After the Treatment of Masseter Muscle Hypertrophy With Botulinum Toxin Type A Injection

Abstract: Purposely strengthening masticatory muscle movement during the denervated atrophic stage of the masseter can prolong the duration of masseter rehypertrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 15 publications
0
29
0
1
Order By: Relevance
“…These complications were grouped together because of their common etiology of localized vascular damage—transient swelling after injection may be caused by the minor rupture of the blood vessels, and bruising is caused by venous or capillary damage during treatment, while hematoma is caused by artery or arteriole puncture without adequate application of pressure. Local swelling is a nonspecific complication of BoNT injections with an incidence rate of around 6.3%‐22.7%, and often recovers in 2 to 3 days . Gaofeng et al reported that local swelling appeared in 5 out of 32 treated patients in the early period after injection and recovered within 1 week.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These complications were grouped together because of their common etiology of localized vascular damage—transient swelling after injection may be caused by the minor rupture of the blood vessels, and bruising is caused by venous or capillary damage during treatment, while hematoma is caused by artery or arteriole puncture without adequate application of pressure. Local swelling is a nonspecific complication of BoNT injections with an incidence rate of around 6.3%‐22.7%, and often recovers in 2 to 3 days . Gaofeng et al reported that local swelling appeared in 5 out of 32 treated patients in the early period after injection and recovered within 1 week.…”
Section: Resultsmentioning
confidence: 99%
“…Pain around the injection site is a common side effect reported by 6 articles. The incidence rate is about 12.5%‐59.1% . Most patients recover within 1‐3 days, though Choe et al reported a patient with persistent local pain that only recovered after 3 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…69,73 There is only one study known at this time to support any of these recommendations, related to masseter muscle treatment only. 74 The study demonstrated that activation of the masseter for a period after injection could lead to improved long-term efficacy. 74 …”
Section: The Influence Of Technique On Abo Efficacymentioning
confidence: 94%
“…74 The study demonstrated that activation of the masseter for a period after injection could lead to improved long-term efficacy. 74 …”
Section: The Influence Of Technique On Abo Efficacymentioning
confidence: 94%
“…The clinical reduction in the masseter muscle and the subsequent reshaping of the lower face can usually be seen after 2‐4 weeks, once the paralyzed muscles have atrophied from lack of use—the physician should therefore inform the patient of the necessary wait. In an MRI evaluation study, muscular atrophy continued into the fourth month with just a single treatment, and recovery was noted by the sixth month …”
Section: Incidence Of Complicationsmentioning
confidence: 99%